2001
DOI: 10.1074/jbc.c100269200
|View full text |Cite
|
Sign up to set email alerts
|

A Glucocorticoid/Retinoic Acid Receptor Chimera That Displays Cytoplasmic/Nuclear Translocation in Response to Retinoic Acid

Abstract: Members of the nuclear receptor superfamily play key roles in a host of physiologic and pathologic processes from embryogenesis to cancer. Some members, including the retinoic acid receptor (RAR), are activated by ligand binding but are unaffected in their subcellular distribution, which is predominantly nuclear. In contrast, several members of the steroid receptor family, including the glucocorticoid receptor, are cytoplasmic and only translocate to the nucleus after ligand binding. We have constructed chimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…It was reported that subcellular localization of CARP is altered by a change of circumstance of the cell, such as serum depletion in vitro (20). Since the function of protein is sometimes regulated by its subcellular localization (25,26), detailed analysis of DARP localization may provide important clues to clarify the physiological function of DARP.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that subcellular localization of CARP is altered by a change of circumstance of the cell, such as serum depletion in vitro (20). Since the function of protein is sometimes regulated by its subcellular localization (25,26), detailed analysis of DARP localization may provide important clues to clarify the physiological function of DARP.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, receptors have been shown to accumulate in distinct nuclear foci in the presence of ligand (van Steensel et al, 1995). Intracellular trafficking and subcellular or subnuclear compartmentalization may be a general phenomenon of type II nuclear hormone receptors and could be differentially influenced by ligand interaction, association with cofactors and/or through heterodimerization with RXR (Baumann et al, 2001b;Mackem et al, 2001;Akiyama et al, 2002;Barsony and Prufer, 2002;.…”
mentioning
confidence: 99%
“…pCI-nGFP-C656G containing a polylinker replacing sites downstream of the coding region of helix 1 of the LBD of rGR [17] was digested sequentially with StuI and EcoRI at the polylinker. The ERā£ expression vector HEGO was digested with BlpI and the overhang filled in prior to digestion with EcoRI.…”
Section: Construction Of Chimeric Receptorsmentioning
confidence: 99%
“…Like other nuclear receptors, the estrogen receptor shuttles between the cytoplasm and the nucleus but its constitutive location is predominantly nuclear [12][13][14][15][16], so it does not undergo translocation to the nucleus in response to ligand. Our earlier studies showed that the translocation properties of GR can be conferred to the ligand binding domain of another nuclear receptor, the retinoic acid receptor [17]. We therefore initiated efforts to generalize the concept that the intrinsic translocation properties of GR can be transferred to non-translocating receptors.…”
Section: Introductionmentioning
confidence: 98%